PENDIDIKAN PRANIKAH MENINGKATKAN KESIAPAN MENGHADAPI KEHAMILAN - Siti Rochimatul Lailiyah; Lelly Aprillia Vidayati; alis nur diana; Siti Mukminah; Dwi Wahyuning Tiyas (Jurnal Medicare, 2026)
Readiness for pregnancy should be established during the premarital period to reduce the risk of adverse pregnancy outcomes resulting from inadequate physical, psychological, and knowledge preparedness. A preliminary study conducted at the Labang District Office of Religious Affairs (KUA), Bangkalan, found that most prospective brides were not adequately prepared for pregnancy. This study aimed to analyze the effect of premarital education on pregnancy readiness among prospective brides. A pre-experimental one-group pre-test and post-test design was employed involving 28 prospective brides. The intervention consisted of a ±20-minute premarital education session using a flipchart. Data were collected through a structured questionnaire and analyzed using the Wilcoxon Signed Rank Test. Before the intervention, 71.4% of participants were categorized as unprepared, whereas after the intervention, 53.6% were classified as prepared. The mean readiness score increased from 22.79 to 37.07 (p = 0.001). Premarital education significantly improved pregnancy readiness and is recommended as a routine program at the Office of Religious Affairs (KUA) to support healthy pregnancy planning.